Typologies and influencing factors in the absorption of European funding for sustainable rural development - Ana-Maria Opria (Regional Studies, Regional Science, 2025)
Sustainable rural development is a key European goal, supported by the Common Agricultural Policy (CAP) since 1962, which provides EU Member States with funds for financing economic and social development projects in rural communities. Research has shown varying capacities among rural communities to absorb these funds, leading to growing disparities. This paper aims to analyse rural fund absorption and classify rural communities based on their performance during two funding periods (2007–2013 and 2014–2020). The study, focusing on Romania, examines factors influencing different absorption performances using data from the National Rural Development Programme, funded by the European Agricultural Fund for Rural Development (EAFRD). The study highlights that different mechanisms are at work in different regions and there is a need to build analysis at the local level in order to better understand the performance of territories and, most importantly, what is needed to boost their performance and ensure sustainable development.